Mathematical equations for modelling soil-water characteristic curve - N. J. Bello; Alfrendo Satyanaga; Gerarldo Davin Aventian; Sung-Woo Moon; Jong Kim (CRC Press, 2023)
Climate change is continuously becoming a vivid global problem that needs to be tackled from every angle for the survival of our planet. Landslide is one of the fore-front phenomena attributed to climate change, claiming lives, and destroying the environment across the globe. To prevent the occurrences of those slides, a good understanding of unsaturated soil is necessary. Soil-water characteristic curve (SWCC) which describes the amount of water retained by a particular soil is an important hydraulic property of the soil, especially related to the soil's pores sizes and spaces connection within it. Modeling water distribution and flow in unsaturated soils requires knowledge of the SWCC which plays a critical role in water management and in prediction of its transport within the soil. There are many attempts to model SWCC mathematically, with the likes of the Satyanaga, Zhai, Fredlund and Xing, Van Genutchen, Brooks and Corey, and several other models for soils with unimodal and bimodal characteristics. Each equation has its own advantage and disadvantage which can model certain type of soil due to the variability of soil properties. It is however important to analyze the available models, study their best applicable scenario and limitations. This paper will therefore study and review several available mathematical equations for modelling SWCC.
Keywords: Mathematics; Applied mathematics; Calculus (dental); Environmental science; Soil science; Hydrology (agriculture); Geology; Geotechnical engineering; Medicine; Dentistry; type of access: open access